2022
DOI: 10.3389/fpls.2022.926953
|View full text |Cite
|
Sign up to set email alerts
|

A Key Molecular Regulator, RNA G-Quadruplex and Its Function in Plants

Abstract: RNA structure plays key roles in plant growth, development, and adaptation. One of the complex RNA structures is the RNA G-quadruplex (RG4) where guanine-rich sequences are folded into two or more layers of G-quartets. Previous computational predictions of RG4 revealed that it is widespread across the whole transcriptomes in many plant species, raising the hypothesis that RG4 is likely to be an important regulatory motif in plants. Recently, with the advances in both high-throughput sequencing and cell imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Transient reporter gene assay further revealed that this G4 inhibits translation, but not the transcription of the ATR gene in living plants [ 31 ]. G4s also have potential in applied/agronomic science, as it is believed that their formation and stability (and thereby the expression of genes containing PQS) could be affected by environmental conditions, e.g., macronutrient availability (mainly K + and Na + ions) and/or drought [ 30 ], temperature [ 32 ], irradiation [ 33 ], etc. From this point of view, it would be interesting to know which genes and pathways contain the highest amount/frequencies of PQS.…”
Section: Discussionmentioning
confidence: 99%
“…Transient reporter gene assay further revealed that this G4 inhibits translation, but not the transcription of the ATR gene in living plants [ 31 ]. G4s also have potential in applied/agronomic science, as it is believed that their formation and stability (and thereby the expression of genes containing PQS) could be affected by environmental conditions, e.g., macronutrient availability (mainly K + and Na + ions) and/or drought [ 30 ], temperature [ 32 ], irradiation [ 33 ], etc. From this point of view, it would be interesting to know which genes and pathways contain the highest amount/frequencies of PQS.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, G4 and rG4 motifs appear widespread, but detecting them in vivo remains challenging, and their potential biological roles remain to be better understood (Griffin & Bass, 2018; Liu et al., 2022; Ma et al., 2022; Volnà et al., 2021). It was recently demonstrated that rG4 structures exist in vivo and can act as regulators (Yang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the crucial role of rhizobial tDRs in regulating nodulation is now ascertained (Ren et al, 2019). The existence of tDRs associated with Argonaute proteins was described (Alves et al, 2017;Cognat et al, 2017;Loss-Morais et al, 2013), and a report showed that AGO1associated tDRs can target and cleave transposable elements (Martinez et al, 2017). Hsieh and colleagues provided evidence that some tDRs are upregulated upon phosphate starvation (Hsieh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The pepino mosaic virus (PMV), which is threat to tomato production, contains pseudoknot structures in the 3′ UTR that overlap with the PolyA tail that is crucial for the replication of PMV RNA [ 153 ]. For more details, the roles of RNA conformers in plants are discussed in the articles by Liu et al [ 154 ], Griffin et al [ 155 ] and Yadav et al [ 156 ].…”
Section: Discussionmentioning
confidence: 99%